Characteristics of castables incorporating highly porous alumina aggregates fabricated by high-temperature evaporation method. Issue 10 (July 2019) - Daimu, Muto; Hashimoto, Shinobu; Daiko, Yusuke; Honda, Sawao; Iwamoto, Yuji
Abstract: Porous alumina aggregates were prepared for use in adiabatic refractories via a high-temperature evaporation method. The mechanical and thermal characteristics of the porous alumina bodies and of castable refractories made using the alumina as an aggregate were investigated. Specimens were produced by adding boron hydroxide, sodium carbonate and water glass to aluminum hydroxide powder compacts in varying proportions, followed by heating at 1700 °C for 1 h in a reducing atmosphere to form porous alumina bodies. During heating, these additives formed a Na2 O-B2 O3 -SiO2 liquid glass phase that promoted the growth of alumina platelets. These platelets subsequently formed a "house of cards" structure. The porosity and compressive strength of the resulting porous alumina were 69.8% and 1.8 MPa, while the thermal conductivity of this material was 0.23 W m −1 ·K −1 at 1000 °C. A castable incorporating the porous alumina aggregate exhibited improved mechanical strength, higher heat resistance and greater FeO corrosion resistance than a sample made using a CA6 (CaO∙6Al2 O3 ) aggregate. The porous alumina castable exhibited similar thermal conductivity to that of the CA6 castable at high temperatures, with a value of 0.85 W m −1 ·K −1 at 1400 °C. Hence, the porous alumina aggregate fabricated in this study can be expected to have practical applications.